Towards a nomadic utopianism: Gilles Deleuze and the good place that is no place - Bell, David Martin (2013)
This thesis utilises the philosophy of Gilles Deleuze alongside theory from the field of 'utopian studies' in order to think through how the concepts of utopia and utopianism might be relevant in an age that seems to have given up on the future. It develops – and argues in favour of - a 'nomadic utopianism', which proceeds through non-hierarchical organisation, maximises what Deleuze calls 'difference-in-itself and creates new forms of living as it proceeds. From this, nomadic utopias are produced, meaning that the relationship between utopianism and utopia IS inverted, such that the former is ontologically prior to the latter. I show how such an approach maintains an etymological fidelity to the concept of utopia as 'the good place that is no place'. I also develop the concept of 'state utopianism', in which a utopian vision functions as a 'perfect', transcendent lack orienting political organisation to its realisation and reproduction. I argue that this is a dystopian politics, and consequently that the state utopia is a dystopia. Contrary to received wisdom - which sees today's 'capitalist realism' as anti-utopian – I argues that the contemporary world can be seen as a state utopia in which 'there is no alternative'. This makes utopia a central force in contemporary ideology. These two forms should not be seen simply as opposites, however, and this thesis also shows how nomadic utopias can ossify into state utopias through the emergence of tyrannies of habit. These theoretical concepts are then applied to works of utopian and dystopian literature (Yevgeny Zamyatin's We, Albert Meister's The so-called utopia of the centre beaubourg and Ursula K. Le Guin's The Dispossessed); and the practices of 'musicking' (with a focus on the symphony orchestra and collective improvisation) and education. It is hoped that this will offer a new way of theorising utopia and utopianism, as well as generating a productive political approach from the thought of Gilles Deleuze, and contributing to debates on the political function of musical and educational practice.